FORMULATION AND IN-VITRO/EX-VIVO CHARACTERIZATIONS OF MICROEMULSION-BASED HYDROGEL FORMULATION OF ACECLOFENAC FOR TOPICAL APPLICATION - Ahmed, Abdul Baquee; Ahmed, Rowshan; Sengupta, Rupa (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: In this study, microemulsion-based hydrogel (MBH) formulation of aceclofenac was prepared for topical administration in the management of pain and inflammation to overcome the gastrointestinal toxicity of the drug occurs with oral administration. Methods: The MBH formulation was prepared by two-step methods. In the first step, the drug loaded o/w microemulsion was prepared first by titration method and in the second step; xanthan gum was added slowly to the microemulsion under homogenization to produce clear MBH. The developed MBH formulations were characterized by in-vitro evaluations, stability studies, and skin irritancy test. The ex-vivo permeation across rat epidermis using modified Keshary-Chien diffusion cell and anti-inflammatory activity of the selected MBH formulation was also evaluated in rat hind paw edema model. Results: The developed MBH formulations showed good stability and acceptable physicochemical properties. The selected formulation (MBH2) showed the highest skin permeation rate (transdermal flux, 193.59±5.01 µg/cm /h; lag time, 0.80±0.01 h) and a maximum of 70.96% inhibition of the hind paw edema was measured after 8 h of the study. 2 Conclusion: Thus, the results obtained in this study suggest the feasibility of the MBH formulation of aceclofenac for topical application for the treatment of pain and inflammation. Keywords: Aceclofenac, Microemulsion-based hydrogel, Transdermal flux, Ex-vivo permeation.